Avenues for Export Diversification : Issues for Low-Income Countries - Brenton, Paul; Newfarmer, Richard; Walkenhorst, Peter (World Bank, Washington, DC, 2017)
While diversification of exports is often a desirable trade objective, it is far from clear how best to tap into new opportunities. This paper discusses the range of avenues of diversification, including (i) expanding the range of markets into which existing products are sold (geographic diversification); (ii) upgrading the value of existing products, including agricultural exports (quality diversification); and (iii) taking advantage of opportunities to expand non-merchandise exports (services diversification), in addition to introducing entirely new export products. All offer opportunities for cost?effective positive policies relating to the incentive regime, backbone services, and export support institutions.